Differential operators determining solutions of Elliptic equations - Aleksandrovich, I. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We construct differential operatorsLg(z), Kg(z), Nf¯(z), Mf¯z) which map arbitrary functions holomorphic in a simply connected domainD of the planez=x+iy into regular solutions of the equation W_zz + A(z,z)W_z + B(z,z)W = 0 and present examples of the application of these differential operators to the solution of fundamental boundary-value problems in mathematical physics.